PERAN GURU DALAM MEMBENTUK KARAKTER KEBHINEKAAN GLOBAL DI SEKOLAH DASAR (JS (JURNAL SEKOLAH), 2025)
Abstract: This study aims to analyze the implementation of diversity values ​​in learning by elementary school teachers. The background of the study is based on the importance of multicultural education in forming students' tolerant, inclusive, and fair characters from an early age. This study uses a descriptive qualitative approach with data collection techniques through observation and interviews. The results of the observation show that teachers have implemented most of the diversity learning indicators with an achievement percentage of 75%, which is categorized as good. Teachers actively introduce local and national cultures, encourage cross-cultural communication, and instill the principle of social justice in the classroom environment. However, the aspect of reflection on students' diversity experiences has not been fully implemented. In conclusion, teachers have played a strategic role in integrating diversity values ​​through contextual and participatory learning approaches, which support the formation of the Pancasila Student Profile characterKeywords: Role of Teachers, Diversity Character, Elementary School Abstrak: Penelitian ini bertujuan untuk menganalisis implementasi nilai-nilai kebhinekaan dalam pembelajaran oleh guru sekolah dasar. Latar belakang penelitian didasarkan pada pentingnya pendidikan multikultural dalam membentuk karakter siswa yang toleran, inklusif, dan adil sejak dini. Penelitian ini menggunakan pendekatan kualitatif deskriptif dengan teknik pengumpulan data melalui observasi dan wawancara. Hasil observasi menunjukkan bahwa guru telah melaksanakan sebagian besar indikator pembelajaran kebhinekaan dengan persentase capaian sebesar 75%, yang tergolong dalam kategori baik. Guru secara aktif mengenalkan budaya lokal dan nasional, mendorong komunikasi lintas budaya, serta menanamkan prinsip keadilan sosial dalam lingkungan kelas. Meskipun demikian, aspek refleksi terhadap pengalaman kebhinekaan siswa belum sepenuhnya diterapkan. Kesimpulannya, guru telah menjalankan peran strategis dalam mengintegrasikan nilai-nilai kebhinekaan melalui pendekatan pembelajaran kontekstual dan partisipatif, yang mendukung pembentukan karakter Profil Pelajar Pancasila.Kata Kunci: Peran Guru, Karakter Kebhinekaan, Sekolah Dasar